Entraves no acesso à saúde para pessoas não binárias e multiplicidade ontológica legal em territórios brasileiros - Bonassi, Brune Camillo (2023)
Access to healthcare for non-cissexual populations in Brazil faces several obstacles. In general, structural prejudice, the non-availability of medications for hormonal therapy, the lack of team training in the professional teams, the absence of a singular therapeutic project, and the long history of pathologization have a direct impact on that. In non-binary people, other factors hinder this access, such as the lack of intelligibility that leads professionals to seek to hormonize in a binary way, with the same protocols; or, even, the architecture of health centers and other places in the network, which, by offering only binary bathrooms, exert a silent and cisnormative pressure on bodies. This thesis aimed to map this field, which so little research has covered. More specifically: a) raise questions about non-binary “identity” in public policies, b) historically contextualize the perverse trail of pathologization and arising body effects; and c) launch proposals to improve the reception and care of non-binary people in the public health network. Its justification lies in the need to observe and enforce the guarantees of a fundamental right, which is access to health, regardless of gender identity. Its methodological inspiration was the feminist autoethnographic practice and gender studies, where I used the creative force of critical fabulation to bring back the history of pathologization, but this time looking at nonbinary populations. The main contributions are in the field of public health policies, although it is possible to find philosophical problematizations that can be expanded to other fields, mainly civil law. This thesis is a material where professionals can seek information for their training, as well as users can find out about their rights.